2016
DOI: 10.1007/s10714-016-2176-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearly charged dilatonic black holes and their Brans–Dicke counterpart: energy dependent spacetime

Abstract: Regarding the wide applications of dilaton gravity in the presence of electrodynamics, we introduce a suitable Lagrangian for the coupling of dilaton with gauge field. There are various Lagrangians which show the coupling between scalar fields and electrodynamics with correct special situations. In this paper, taking into account conformal transformation of Brans-Dicke theory with an electrodynamics Lagrangian, we show that how scalar field should couple with electrodynamics in dilaton gravity. In other words,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 69 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…It is a matter of calculation to show that there is no consistent conformal transformation between the actions (1) and (23) [74]. In other words, although the action (1) leads to the well-known action of Maxwell-dilaton gravity for β → ∞, it is not conformally related to the BD-BI action, and therefore, Eq.…”
Section: Black Hole Solutions In Bd-bi Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a matter of calculation to show that there is no consistent conformal transformation between the actions (1) and (23) [74]. In other words, although the action (1) leads to the well-known action of Maxwell-dilaton gravity for β → ∞, it is not conformally related to the BD-BI action, and therefore, Eq.…”
Section: Black Hole Solutions In Bd-bi Gravitymentioning
confidence: 99%
“…Considering the conformally ill-defined action (1), in the next section, we follow the method of Ref. [74] to obtain a conformally well-defined action of BI-dilaton gravity.…”
Section: Black Hole Solutions In Bd-bi Gravitymentioning
confidence: 99%
“…The Einstein-BI-dilaton gravity action and its related field equations can be obtained from the BD-BI action and its related field equations by applying the mentioned conformal transformation [17]:…”
Section: Field Equation Andmentioning
confidence: 99%
“…It was shown that the proper potential is a Liouville-type one with both topological and BI correction terms, as [17] V (Φ) = 2Λ exp ( 4 Φ − 1 )…”
Section: Einstein Framementioning
confidence: 99%
See 1 more Smart Citation